Modern Implant Surface Engineering for Optimized Osseointegration and Prevention of Peri-Implant Diseases: a Narrative Review - Jędras, Aleksandra; Czerepak, Gabriela; Pociask, Weronika; Bednarz, Katarzyna; Zowczak, Wiktoria; Gliwa, Katarzyna; Czajkowska, Weronika (Quality in Sport, 2026)
Introduction Dental implant therapy has become a predictable and widely accepted treatment modality for the restoration of oral function and aesthetics. Despite high long-term survival rates, biological complications such as peri-implant mucositis and peri-implantitis remain significant challenges that may compromise implant stability and patient quality of life. Implant surface characteristics play a crucial role in both osseointegration and microbial colonization, creating a complex balance between enhanced bone integration and resistance to biofilm formation. This narrative review aims to provide a comprehensive overview of current strategies in dental implant surface engineering with regard to their dual role in promoting osseointegration and preventing peri-implant diseases. Materials and Methods Literature published between 2020 and 2025 was analyzed using PubMed, Scopus, and Web of Science databases. Results The review discusses the influence of surface topography, roughness, chemistry, and wettability on biological responses at the implant interface. Furthermore, contemporary modification strategies, including bioactive ceramic coatings, ion and nanoparticle incorporation, nanotopography, anodization, and laser surface treatments, are critically evaluated. Emerging multifunctional approaches combining osteogenic and antimicrobial properties are also highlighted. Conclusions Current evidence suggests that no single surface modification fully optimizes both osseointegration and bacterial resistance. However, advanced nanostructured and laser-modified surfaces demonstrate promising potential for improving long-term implant performance. Future progress in implantology will likely depend on integrating biomaterial innovations with individualized clinical approaches and long-term evidence-based evaluation.